Analisis Eksplorasi terhadap Pola Transaksi Ekonomi Syariah dalam Praktik Jasa Titip (Jastip) atau Personal Shopper - Ahmad Iqbal Fathoni (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
Personal Shopper or JASTIP is one of today's Islamic economic products. Where many people conduct economic transactions using this pattern because of its convenience and time efficiency. Of course, the progress and development of innovation in this economic field must be balanced with legal certainty in the field of Islamic economics. In general, buying and selling transactions through this JASTIP pattern are in accordance with the theory of wakalah and murobahah in Islamic economics. However, at the technical level, this JASTIP pattern has three methods of payment and procurement of goods, First, the order-pay-send method. Second, the order by request method. Third, the order first-pay later method. The JASTIP pattern with the Order-Pay-Send method includes a wakalah bil ujroh contract. While the JASTIP pattern with the Order by Request method includes a Murobahah contract. And the JASTIP pattern with the Order First-Pay Later method includes the Bai' dain bi al-dain contract.